SDN Communication Quality Assurance Strategy witb DDoS Defense and Routing Optimization - Jiahua Zhang; Zhongxue Yang; Jiangping Wang; Yukai Shi; Liang Wei (Dianxin kexue)
A SDN communication quality assurance strategy which organic combines DDoS threat identification with route optimization was put forward.It means,when the intent link was congestive attacked by DDoS,it wi11 identify and filter the abnormal data packet,and wi11 generate optimized routing to ensure the quality of network communications.First of a11,a distributed intrusion detection system under SDN framework was designed.The system realizes the detection recognition,filtration and treatment about the DDoS threat,such as cheating message,excepting message and destroying message.Secondly,a kind of best algorithm about generating routing path was realized.The experimental result shows that the network deployment plan which mentioned in this paper,can identify and filter the aggressive data packet,and the average network data transmission delay doesn't increase sharply when the network is under attack.